HPLC and DNA barcoding profiles for identification of the selected twelve Mucuna species and its application for detecting prohibited aphrodisiac Mucuna products - Aekkhaluck Intharuksa; Jessada Denduangboripant; Sunee Chansakaow; Kannika Thongkhao; Suchada Sukrong (Heliyon, 2023)
Aphrodisiac herbal products originated from various plants including Mucuna species. In Thai folklore, Mucuna macrocarpa Wall. and M. pruriens (L.) DC. have long been consumed and utilized for their aphrodisiac properties. Consumption of these plants can lead to serious adverse effects caused by l-dopa. The plants have been legally banned for use as foods, dietary supplements, or nutraceuticals by the FDA of several countries. To protect consumers, methods for the identification of illicit plants or herbal products are needed. This study aimed to identify the selected twelve Mucuna species and examine the aphrodisiac herbal products containing M. macrocarpa and M. pruriens by using HPLC analysis of l-dopa coupled with DNA barcoding profiles of ITS, matK, rbcL, and trnH-psbA. The results showed that l-dopa could be found not only in the seeds of M. macrocarpa and M. pruriens but also in associated allied Mucuna species. Then, a DNA barcode was introduced to support in HPLC profiling to identify the plants. DNA barcodes of twelve Mucuna species found in Thailand were established and used to reconstruct a phylogenetic tree. In this study, ITS2 sequences showed the highest interspecific variability and could be used to differentiate all Mucuna species. The results of ITS2 sequence coupled with HPLC analysis revealed that all the purchased aphrodisiac products originated from M. pruriens only. Therefore, the integration of HPLC analysis and DNA barcoding profile was an efficient method for the identification of prohibited Mucuna species for safety monitoring of herbal supplements and protecting customer safety. Regulatory agencies should raise awareness and restrain the use of these commercial products.